Analisis Preferensi Pemilihan â€œKos-Kosanâ€ Mahasiswa Universitas Negeri Semarang Tahun 2018 - Nuruliyah, Devti; Aji, ananto (Edu Geography, 2019)
This reaseach aims to: (1) find out the factors that influence students in choosing boarding houses and the factor that become their main preferences. (2) measuring the level of student satisfaction with the boarding house which they occupied. These are factor analysis and descriptive analysis of percentage. Factor analysis is to answer the objective number 1 and descriptive analysis of percentage is to answer the objective number 2. The results showed that there are four main factors that influence students in choosing their boarding houses. These are environmental sanitation factor, price and facilities factor, safety factor, also accessibility and reference groups factor. The preference of students to choose boarding houses for environmental sanitation factors is the highest. It can be seen from the eigenvalue of environmental sanitation factors which has 2,964. This is the largest eigenvalue of the other factors. Meanwhile, the percentage of variability of variance has 29,641% and the amount of loading factor of three components are the largest. These are 0,915, 0,953 and 0,893 Penelitian ini bertujuan untuk: (1) mengetahui faktor-faktor yang mempengaruhi mahasiswa dalam memilih tempat kos dan faktor yang menjadi preferensi utamanya. (2) mengukur tingkat kepuasan mahasiswa terhadap kos yang ditempatinya. Terdapat dua teknik analisis yang digunakan dalam penelitian ini yakni analisis faktor untuk menjawab tujuan 1, dan analisis deskriptif untuk menjawab tujuan 2. Hasil penelitian menunjukkan bahwa terdapat empat faktor utama yang mempengaruhi mahasiswa dalam memilih tempat kosnya, yakni faktor sanitasi lingkungan, faktor harga dan fasilitas, faktor keamanan, serta faktor aksesibilitas dan kelompok referensi. Preferensi/kecenderungan mahasiswa dalam memilih kos terhadap faktor sanitasi lingkungan adalah yang tertinggi, hal ini dapat diketahui dari eigenvalue faktor sanitasi lingkungan yakni sebesar 2,964, yang mana merupakan eigenvalue terbesar daripada faktor-faktor yang lain, keragaman variannya sebesar 29,641 %, dan nilai loading factor ketiga komponen faktornya adalah yang terbesar yakni 0,915, 0,953, dan 0,893.